2012
DOI: 10.1016/j.wpi.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Use of prediction methods for patent and trademark applications in Spain

Abstract: Patent and trademark offices which run according to principles of new management have an inherent need for dependable forecasting data in planning capacity and service levels. The ability of the Spanish Office of Patents and Trademarks to carry out efficient planning of its resource needs requires the use of methods which allow it to predict the changes in the number of patent and trademark applications at different time horizons. The approach for the prediction of time series of Spanish patents and trademarks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…We focus on years, during which Spain has experienced a steady economic growth, investment expansion and catching up to the advanced nations, which came to a halt with the arrival of the 2008 global financial crisis (Prados de la Escosura, 2017). This trend has reversed after 2008, a structural break particularly visible in patenting (Belda et al, 2014; Hidalgo & Gabaly, 2012). Hence, relating pre‐2008 collaboration patterns to post‐2008 patenting may not be comparable with the pre‐2008 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We focus on years, during which Spain has experienced a steady economic growth, investment expansion and catching up to the advanced nations, which came to a halt with the arrival of the 2008 global financial crisis (Prados de la Escosura, 2017). This trend has reversed after 2008, a structural break particularly visible in patenting (Belda et al, 2014; Hidalgo & Gabaly, 2012). Hence, relating pre‐2008 collaboration patterns to post‐2008 patenting may not be comparable with the pre‐2008 analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The years where there is a lower numbers of grants are relatively many more when compared to the years with higher numbers of patents. Several studies have shown that it is possible to model the series of patents with ARIMA [41][42][43][44]. Some satisfactory model adjustments can be required to decrease the model residuals.…”
Section: Methods and The Case Studymentioning
confidence: 99%
“…First, through "(A) Time Series Analysis (TSA)", the frequency of patent applications by technology was extracted as time series data to predict promising future technology [21,24,[28][29][30][31]34,[38][39][40][41][42][43][44]. Then, through "(B) Social Network Analysis (SNA)", the relationship between nodes as a quantitative indicator through centrality indices was extracted, and promising detailed descriptive areas based on the extracted indicators were predicted [22,[24][25][26][27][28][29][30][31][32]34,39,40,43,[45][46][47][48][49][50]. In addition to the quantitative analysis methods, the qualitative analysis method of "(C) Technology Mapping Analysis (TM)" was also used in previous studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the quantitative analysis methods, the qualitative analysis method of "(C) Technology Mapping Analysis (TM)" was also used in previous studies. Through "(C) Technology Mapping Analysis (TM)", the importance of the level of technology for each area was obtained, and priorities for technology development were identified [21,24,[29][30][31]38,40,[45][46][47][48][49][50][51]. In addition to predicting promising technology, previous studies have identified vacant technology by analyzing patent information of analysis target nodes through "(D) Generative Topographic Mapping Analysis (GTM)", identifying empty technology [24,27,28,40,52].…”
Section: Literature Reviewmentioning
confidence: 99%